Thromboprofilaxys With Fondaparinux vs. Enoxaparin in Hospitalized COVID-19 Patients: A Multicenter Italian Observational Study - Russo, Vincenzo; Cardillo, Giuseppe; Viggiano, Giuseppe Vito; Mangiacapra, Sara; Cavalli, Antonella; Fontanella, Andrea; Agrusta, Federica; Bellizzi, Annamaria; Amitrano, Maria; Iannuzzo, Mariateresa; Sacco, Clara; Lodigiani, Corrado; et al. (Frontiers in Medicine, 2020)
Importance: The use of anticoagulant therapy with heparins decreased mortality in hospitalized patients with COVID-19. Even if enoxaparin and fondaparinux have the same clinical indication for venous thromboembolism (VTE) prevention. To date, few data about the use of fondaparinux, in term of safety among COVID-19 patients are present. Objective:To evaluate the safety and clinical impact of VTE prophylaxis with fondaparinux and enoxaparin among COVID-19 patients hospitalized in internal medicine units. Design and Participants: This was a retrospective multicenter observational study including symptomatic patients with COVID-19 admitted to internal medicine units in Italian hospitals. Main Outcomes: The primary safety outcome was the composite of major bleeding (MB) and clinically relevant non major bleeding (CRNMB); the primary effectiveness outcome was the composite of all events classified as pulmonary embolism (PE)and deep venous thrombosis (DVT). The secondary effectiveness outcome included acute respiratory distress syndrome (ARDS) and all-cause death. Results:Among 120 COVID-19 patients enrolled in the study, 74 was taking enoxaparin (4.000 or 6.000 units/day) and 46 fondaparinux (2.5 units/day).During a median follow-up of 32 (IQR: 14- 51) days, the cumulative incidence of VTE and bleeding events on pharmacological thromboprophylaxis was 19% and 8% respectively. The incidence of both VTE (6.5% vs 13.5%; P= 0.36) and bleeding events (6.5% vs 4.1%P= 0.68) did not show significant difference between COVID-19 patients on fondaparinux compared to those on enoxaparin therapy. Conclusions: these results need confirmation by prospective studies but provide the preliminary evidence of a safe use of fondaparinux for VTE prophylaxis in hospitalized COVID-19 patients.